Wind-induced slow fading in foliated fixed wireless links - Chua, Tien Han (2012)
This paper investigates the characteristics of wind-induced slow fading in fixed wireless links where the first Fresnel Zone is partially obstructed by trees. Based on results from long term propagation measurements at 5.8GHz, we show that, besides seasonal and fast fading, the received signal in foliated fixed wireless links also experiences temporal fading of the order of minutes. This is contributed by the temporal shadowing effect owing to the mean deflection of the tree canopy under the influence of mean wind speed and direction. The characteristics of the slow fading observed during on- and off-leaf seasons will be presented. The correlation among received signal strength variation, tree canopy movement and wind will be discussed. A simple knife-edge diffraction model will be used to explain the trends observed in the slow fading. The analyses presented are useful for long-term operation of foliated fixed wireless links, the design of slow adaptive fade mitigation schemes and the development of vegetation fading simulators.